Does influenza vaccination help reduce incidence of COVID-19 infection among hospital employees?. Issue 2 (14th January 2022) - Shosha, Soha H.; Ajlan, Dana I.; Al-Ghatam, Rana
Abstract : Abstract: To facilitate the understanding of the interaction between severe acute respiratory syndrome coronavirus 2 causing the corona virus disease 2019 (COVID-19) and other pathogens causing respiratory system affection we investigated the effect of influenza vaccination on the incidence and severity of COVID-19 among members of staff working in the Bahrain Defense Force Hospital. All staff members working in the hospital between February 2020 and March 2021 were divided into 2 main groups based on whether or not they received influenza vaccination. None of the participants had received any of the COVID-19 vaccines throughout this time period. The records of each were scrutinized to see the effect of influenza vaccination on incidence and severity of COVID-19. Severity measures were: need for hospital and intensive care unit admission and total length of hospital stay. Incidence of affection with COVID-19 was much lower in the vaccinated group (3.7% vs 8.1%, P  < .001). Influenza vaccination also reduced total length of hospital stay (6.2 days vs 12.7 days, P  < .05) and need for intensive care unit admission among the patients. Influenza vaccine reduces both the incidence of affection as well as the overall burden of COVID-19. This is of particular importance for people working in the healthcare field during the serious COVID-19 pandemic.